2003
DOI: 10.1002/j.2161-1912.2003.tb00354.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Racial Identity Development and Multicultural Counseling Competency: A Second Look

Abstract: The relationship between racial identity development and multicultural counseling competency across a 2-year period of time was examined in this study. Significant increases were found in multicultural counseling competency but not in their levels of racial identity development across time. Possible explanations for and limitations of this research are discussed.La relacion entre el desarrollo de la identidad racial y la competencia para consejeria multicultural a traves de un periodo de dos atios se examina e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 22 publications
4
23
0
Order By: Relevance
“…For example, one participant marked her race as "White" on the demographic questionnaire, but in the "other" section explained that she was adopted by a Black family when she was young and ethnically self-identified as Black. Research has documented a positive relationship between racial identity and multicultural competence, in which higher levels of racial identity have correlated with higher levels of multicultural counseling competency (Vinson & Neimeyer, 2003). One can logically assume that higher levels of racial identity suggests that an individual has an awareness and understanding of his or her own culture, which, in turn, can affect his or her sensitivity and understanding of the culture of others (Vinson & Neimeyer, 2003).…”
Section: Discussionmentioning
confidence: 97%
“…For example, one participant marked her race as "White" on the demographic questionnaire, but in the "other" section explained that she was adopted by a Black family when she was young and ethnically self-identified as Black. Research has documented a positive relationship between racial identity and multicultural competence, in which higher levels of racial identity have correlated with higher levels of multicultural counseling competency (Vinson & Neimeyer, 2003). One can logically assume that higher levels of racial identity suggests that an individual has an awareness and understanding of his or her own culture, which, in turn, can affect his or her sensitivity and understanding of the culture of others (Vinson & Neimeyer, 2003).…”
Section: Discussionmentioning
confidence: 97%
“…Although the list was further expanded to 34 competencies in 1998, the 31 competencies model has received the most research attention and the endorsement of the American Counseling Association (ACA), the Association for Counselor Education and Supervision (ACES), and two divisions (17 & 45) of the American Psychological Association (Arredondo et al, 1996; D. W. Sue, Arredondo, & McDavis, 1992; D. W. Sue, Bernier, et al, 1982; D. W. Sue, Carter, et al, 1998). There is growing support for the view that the competencies provide guidelines for best practice (Arredondo, 1998;Corey, 1996;Vinson & Neimeyer, 2003). Specifically, Multicultural Counseling Competence III.C.7 appears to support the need for counselors to take responsibility for acknowledging cultural factors present in the counseling relationship (D. W. Sue et al, 1992), which we conceptualized as the broaching process.…”
Section: Broaching Race As a Multicultural Competencementioning
confidence: 95%
“…Racial/ethnic minority counselors have consistently been found to describe themselves as more multiculturally competent than do White Americans in several samples, including counseling/clinical psychology students Vinson & Neimeyer, 2003), vocational rehabilitation counselors (Bellini, 2002), and APA-approved university counseling center staff members (Sodowsky, Kuo-Jackson, Richardson, & Corey, 1998). This racial/ethnic difference was also cross-validated by the CCCI-R, an other-report multicultural counseling instrument (Constantine, 2001c).…”
Section: Criterion Validity Of the Mcse-rd Scoresmentioning
confidence: 95%
“…Findings from prior research (e.g., Bellini, 2002;Vinson & Neimeyer, 2003) and the current study have suggested that racial/ethnic minority counseling students and professionals tend to receive more multicultural counseling training and have a higher proportion of minority clients on their caseloads, which may, in turn, lead to higher perceived abilities to perform multicultural counseling Pope-Davis et al, 1994). In other words, the racial differences on multicultural counseling competency or self-efficacy may be due to how much multicultural counseling training and other relevant experience a counselor receives rather than being due to his or her race per se.…”
Section: Criterion Validity Of the Mcse-rd Scoresmentioning
confidence: 99%